Prevalence of delayed first permanent molar eruption among children 7 to 9 years old - Hamsin, Noor Hamiza Hani; Indriyanti, Ratna; Musnamirwan, Iwan Ahmad (Faculty of Dentistry Universitas Padjadjaran, 2014)
Introduction: Eruption is the moment of tooth emergence into the oral cavity. The emergence of the first permanent molar was followed by shedding of the deciduous incisors and as for permanent incisors eruption; it was taken as a point where the transition from primary dentition to permanent dentition begins with. The aim of this research is to determine the prevalence of delayed first permanent molar tooth eruption that occur among the children from 7 to 9 years old in Sekolah Dasar Negeri (SDN) Cisitu 1, SDN Coblong 4 and SDN Sekeloa 1. Methods: The method of choosing sample was simple random sampling. Out of 547 children from three Sekolah Dasar Negeri (SDN), only 71 children were selected randomly according to their ages, 7 to 9 years old. The method of this research was descriptive with surveying method. A clinical examination was done to determine the tooth eruption and data information was taken. Results: Out of 547 children from SDN Sekeloa 1, SDN Cisitu 1 and SDN Coblong 4 only 71 children were selected to take part in this research. They were randomly selected according to their age from 7 to 9 years old from each school Conclusion: This research shows that the delayed first permanent molar eruption among children in these samples of population were rarely happen.